Produção de cerveja do tipo pilsen com adição de capim-cidreira (Cymbopogon citratus) - Lahm, Veronica Steinmetz (2023)
Beer is a drink produced by the fermentation of brewer's wort, a mixture of water, malted barley or malt extract, and hops, with the addition of yeast. In Brazil, we have seen growth in the production and consumption of craft beers, although this segment still represents a small portion in relation to large industries. This has led to an increase in the number of microbreweries, reflecting the evolution of the sector. This study aimed to produce a craft Pilsen beer with the addition of an aqueous extract of lemongrass cryoconcentrate (Cymbopogon citratus) and evaluate its physicochemical characteristics. The aqueous extract was produced through maceration, followed by percolation for 24 hours (10% m/V), filtration and cryoconcentration by centrifugation. The beer was produced with Vienna, Munich I and Pilsen malts, Crystal mineral water, Magnum hops and W34-70 yeast. Analyzes were carried out to determine the pH, soluble solids content, color and alcohol content of the beer. The results were as expected, with a Ph of 4.6, soluble solids content of 3.5, alcohol content of 5.2%, acidity of 0,05% and a yellowish color. There is a similarity between commercial beer and beer produced with lemongrass.